Studi Eksperimental Refrigerator Cryogenic Joule-Thomson Menggunakan Kompresor Termik Sistem Adsorpsi - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Kedokteran Hewan UGM, 2000)
Sorption refrigerator is based on the ability of porous materials to chemically or physically adsorb large quantities of gases. As the sorbent is sequentially heated and cooled, the gas is alternately exhausted from the sorbent at high pressure or readsorbed at low pressure respectively. By successively heating and cooling a number of sorbent beds, a steady stream of refrigerant gas provided to a conventional closed cycle Joule Thomson refrigeration expansion stage. This work presents experimental results of a prototype Joule Thomson cryogenic refrigerator operating with activated charcoal P VDC / nitrogen thermal sorption compressors. Cold temperatures of the order of 100 K at zero net cooling power has been achieved with compressor cycle time of about 60 minutes. Experimental results, including the evolution of compressor temperature and of gas pressure in the compressor are presented. Due to the absence of moving parts and the simple technology of this system, sorption refrigerator is potential candidate in order to meet the needs for cryogenic refrigeration system in particularly in spaceborne applications. A theoretical model allowing to calculate these evolutions has been established. The experimental results have been compared to the theoretical ones.